Hox transcriptional specificity despite a single class of cofactors: Are flexible interaction modes the key?. (19th December 2012) - Merabet, Samir; Hudry, Bruno
Abstract Editor's suggested further reading in BioEssays ftz Evolution: Findings, hypotheses and speculations (response to DOI10.1002/bies.201100019) Abstract On the border of the homeotic function: Re‐evaluating the controversial role of cofactor‐recruiting motifs Abstract Control of DNA replication: A new facet of Hox proteins? Abstract Classification of sequence signatures: a guide to Hox protein function Abstract